Eemian (MIS 5e) climate oscillations based on palaeobotanical analysis from the Beckentin profile (NE Germany). (20th December 2021) - Hrynowiecka, Anna; Stachowicz-Rybka, Renata; Niska, Monika; Moskal-del Hoyo, Magdalena; Börner, Andreas; Rother, Henrik
Abstract: Climate instability in the Eemian Interglacial is gaining more and more evidence. One of such oscillations in the Beckentin record is indicated by the disappearance of the Cladocera and changes in macroremains at the beginning of E4a ( Corylus phase). They confirm the shallowing of the reservoir, probably caused by climate changes, but not reflected in the palynological record. However, a significant oscillation observed in the first half of the E5 ( Carpinus phase), ~5860 years after the boreal forests subsided and ~6290 years after the onset of interglacial forestation, suggests that, although not being an analogue of the OHO (Older Holsteinian Oscillations) in MIS 11c and the 8.2 ka cold event in the Holocene, it is very similar to these oscillations. The Eemian oscillation was noted also in the Bispingen profile in northern Germany, ~6500 years after the interglacial forestation. However, the course of vegetation changes there differs from that in Beckentin. The analysis of macroremains and Cladocera confirms the disappearance of rush and water vegetation in the water reservoir at that time in Beckentin. These results confirm that numerous climatic oscillations could have occurred in the Eemian Interglacial.